A fuzzy classifier system for fault tolerance - Cerrada, Mariela; Aguilar, José (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
In this work, we propose to use a Fuzzy Classifier System for building a fault tolerance automated system wich determines the applicable and feasible maintenance tasks on industrial plant. This system is based on the ";Reliability-Centered Maintenance"; methodology.